I'm so glad they're going to die: a political reading of the novel The Bell Jar, by Sylvia Plath - Bertacini, Vanessa [UNESP] (Univ Caxias Sul, Graduate Program Literature Culture & Regions, 2020)
Sylvia Plath was a North American writer, especially known by her poetic production and associated with the Confessional Poetry movement. The Bell Jar (1963), her only novel, is constantly read as an autobiography, and Esther's Greenwood's life, read as Plath's own life. In this work, we propose the reading of the novel according to the dialectical approach and the proposals of a political reading promoted by Fredric Jameson, by means of which we can reach an interpretation of Plath's novel that is not achieved by the traditional models of literary interpretation, that is, we sought to show that, through a political reading, it is possible to find the horizons that overcome the idea of an autobiography and reach the political and collective aspect of the novel.
Keywords: Sylvia Plath; The Bell Jar; Political reading